The ethical life of a Japanese - Pursel, Lisle Willetts (My University, 1896)
Introduction: The ancient history of Japan, as recorded in native annals is very untrustworthy because of the mythology, with which it is enshrouded. In these mythical legends, numerous deities play a conspicuous part, the country itself being styled the “Land of the gods.” It is asserted by them that there first existed seven generations of heavenly deities followed by five generations of deities who were in turn succeeded by the mortal sovereigns.
Citation: Pursel, Lisle Willetts. The ethical life of a Japanese. Senior thesis, Kansas State Agricultural College, 1896.
Morse Department of Special Collections
Keywords: History; Japan; Mythology; Sovereigns; Theses; Manuscripts (documents)